2012
DOI: 10.1590/s1516-14392012005000097
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and tensile properties of a recycled AA7050 via spray forming and ECAP/E

Abstract: The aim of this work is to evaluate the conjugation of advanced processing techniques, such as spray forming, extrusion and ECAP as a processing route for reuse of machining chips generated during aircrafts manufacturing parts from AA7050-T7451 raw material plates supplied according to AMS 4050H1 . In this way, the sprayforming process was used for remelting, and billet production, followed by extrusion and ECAP. At the end of the process, an artificial aging according to AMS 2772E 2 was conducted. An assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This kind of morphology was observed also for Ti-Al coatings fabricated by mechanical alloying [11]. Similar dimples are also obtained for samples which were tensile tested [12,13].…”
Section: Resultssupporting
confidence: 81%
“…This kind of morphology was observed also for Ti-Al coatings fabricated by mechanical alloying [11]. Similar dimples are also obtained for samples which were tensile tested [12,13].…”
Section: Resultssupporting
confidence: 81%
“…Nevertheless, in cases where the solubility of the alloying elements is higher in the primary phase, for example, Cu-, Zn-, and Mg-containing Al-alloys, the effect of high cooling rates promoted during the atomization stage may be more preserved in the final microstructure, and other considerations should be made. [25] Several authors reported spray-forming as a rapid solidification process, in which it is possible to obtain extended solid solubility, metastable phases, and even amorphous phases. [17,[26][27][28][29][30][31] Achieving such rapid solidification characteristics is indeed possible by spray-forming.…”
Section: Discussionmentioning
confidence: 99%
“…After conventional mill annealing process, the material's tensile yield strength was reported to be approximately 1150 Mpa. Hyodo et al [256] recycled AA 7050 machine chips using both conventional and direct conversion methods by following the process of spray forming, hot extrusion, and ECAP.…”
Section: Equal Channel Angular Pressing (Ecap)mentioning
confidence: 99%